The antifungal activity of essential oil from Melaleuca leucadendra (L.) L. grown in China and its synergistic effects with conventional antibiotics against Candida. Issue 17 (2nd September 2019) - Zhang, Jing; Wu, Huihui; Jiang, Dan; Yang, Yongan; Tang, Wenjian; Xu, Kehan
Abstract: To identify the natural antifungal agents, the antifungal activities of Melaleuca leucadendra (L.) L. essential oil (ML-EO) from Fujian Province of China were assayed. Treatment of ML-EO in combination with the front-line using antibiotics against Candida led to synergistic effects. Electron microscopy analysis on the oil treated C. albicans cells revealed the formation of mesosome-like structures, suggesting well the membrane damage caused by the essential oil. The Griess assay by monitoring NO production in LPS-stimulated RAW264.7 cells indicated the potent anti-inflammatory activity of ML-EO. In comparison with the marked essential oil of Melaleuca alternifolia EO, ML-EO had almost the same chemical components. In general, the antifungal activity of ML-EO and its synergistic interactions with conventional antibiotics were able to lead the development of new treatment strategies on Candida infection. Abstract :